The Development of Connected Integrated Science Modules based on Differentiated Learning on Solar System Materials - Astiti, Kadek Ayu; Selamet, Kompyang; Herliandry, Luh Devi (Jurnal Pembelajaran Fisika, 2023)
The development of a Connected Type Integrated Science Module based on differentiated learning aims to make it easier for students to understand science concepts in an integrated manner. This is done by connecting one concept to another by increasing analytical skills and realizing independent learning. Modules were developed to link one concept with another science concept to improve analytical skills and realize independent learning for students. This type of research and development (R&D) uses the ADDIE model with the stages of analysis, design, development, implementation and evaluation. The results of the validity test from material and media experts obtained an average score of 88.1 and 81.8 in both categories. The practitioner test was carried out using the module by the teacher and obtained an average score of 81.15 in the good category. The development and analysis results obtained show that the module can be used in the learning process but further research is needed on the practicality of using this module and it needs to be developed into other Integrated Science materials.Keywords: Module, connected type of integrated science, differentiated instruction.DOI: http://dx.doi.org/10.23960/jpf.v11.n2.202301